Crystal structure and magnetic properties of 3, 5-pyridinedicarboxylate-bridged Re(II)M(II) heterodinuclear complexes (M = Cu, Ni and Co). (1st November 2021) - Pacheco, Mario; González-Platas, Javier; Julve, Miguel; Lloret, Francesc; Kremer, Carlos; Cuevas, Alicia
Graphical abstract: Abstract: The use of the mononuclear rhenium(II) precursor NBu4 [Re(NO)Br4 (H2 pydc)]· i -PrOH (1) (H2 pydc = 3, 5-pyridinedicarboxylic acid) as a metalloligand towards Cu(II), Ni(II) and Co(II) afforded three new heterobimetallic complexes [Re(NO)Br4 (μ-Hpydc)Cu(4, 4′-dmbipy)2 ]·(CH3 )2 CO·0.25MeCN (2), [Re(NO)Br4 (μ-Hpydc)Ni(dmphen)2 ]·MeCN (3 ) and [Re(NO)Br4 (μ-Hpydc)Co(dmphen)2 ]·2H2 O (4 ), respectively [4, 4′-dmbipy = 4, 4′-dimethyl-2, 2′-bipyridine, dmphen = 2, 9-dimethyl-1, 10-phenanthroline and Bu4 N + = tetra- n -butylammonium]. The crystal structures of 1 and 2 are reported herein together with the cryomagnetic investigation of 1 –4 in the temperature range of 2.0–300 K. 1 is a mononuclear compound whose structure is made of [Re(NO)Br4 (H2 pydc)] - complex anions, tetra- n -butylammonium cations and isopropanol molecules of crystallization. Each rhenium(II) ion in 1 is six-coordinate with four bromide ligands in the equatorial positions and a nitrosyl group and one pyridyl-nitrogen atom from an H2 pydc ligand filling the axial sites. 2 is a neutral heterobimetallic compound where the [Re(NO)Br4 (Hpydc)] 2- complex anion acts as a monodentate ligand towards the [Cu(4, 4′-dmbipy)2 ] 2+ complex cation through one carboxylate–oxygen atom. The rhenium(II) ion is six-coordinate in a somewhat distorted octahedral surrounding similar to that in 1 . The copper(II) ion in 2 is five-coordinate with four nitrogen atoms from two bidentate 4, 4′-dmbipy ligands and one carboxylate–oxygen atom, describing a surrounding intermediate between square pyramidal and trigonal bipyramidal. Compound 1 behaves as a quasi-magnetically isolated spin doublet with weak antiferromagnetic interactions through space Br⋯Br contacts, ligand field, spin–orbit coupling, tetragonal distortion, and covalence effects considered as variable parameters in a successful simulation of the magnetic data. Compounds 2 –4 exhibit also weak intramolecular antiferromagnetic interactions ( J ) covering the range −0.60(1) to −1.50(1) cm −1 with the Hamiltonian being defined as H = - J S Re S M, M = Cu (2), Ni (3 ) and Co (4 ).